2013
DOI: 10.1177/0143831x13492831
|View full text |Cite
|
Sign up to set email alerts
|

Labour flexibility and innovation, complementary or concurrent strategies? A review of the literature

Abstract: The European strategy for growth has a twofold aim: to become an innovative union and to enhance labour flexibility. Yet, few have addressed the question of whether these two strategies are compatible or concurrent. Through a review of the literature, this article addresses this question by focusing on different types of labour flexibility (functional, contractual and financial), and two types of innovation outcomes: employee-driven innovation (EDI) and organizational innovativeness. Using insights from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Staying with intraorganizational relations, both the collaborative innovation and EDI literatures emphasize the crucial role of opportunities for transformative learning within and across teams and groups of employees. de Spiegelaere, Van Gyes, and Van Hootegem () note that numerous studies have found a relationship between collaboration within multi‐skilled teams and innovativeness. As noted earlier, the EDI literature more generally sees workplace innovation as “a reflexive process, grounded in continuing reflection, learning and… involving employees and managers at all levels” (European Commission , 69).…”
Section: Innovation and The Workplace In Public Servicesmentioning
confidence: 99%
“…Staying with intraorganizational relations, both the collaborative innovation and EDI literatures emphasize the crucial role of opportunities for transformative learning within and across teams and groups of employees. de Spiegelaere, Van Gyes, and Van Hootegem () note that numerous studies have found a relationship between collaboration within multi‐skilled teams and innovativeness. As noted earlier, the EDI literature more generally sees workplace innovation as “a reflexive process, grounded in continuing reflection, learning and… involving employees and managers at all levels” (European Commission , 69).…”
Section: Innovation and The Workplace In Public Servicesmentioning
confidence: 99%
“…Of course, in times of crisis, firms may feel pressured to cut costs in the short term by relying on external flexibility measures. Indeed, trends in the European labour market and EU backed policies do not focus on enhancing functional flexibility, but rather aim to increase external (contractual) and financial flexibility (De Spiegelaere et al, 2014;Eurofound, 2010;Sandor, 2011).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Also, most studies that relate job characteristics (i.e. job complexity, job rotation) to creativity and innovative behaviour are based on cross-sectional designs and single sources (see Hammond et al, 2011;Shalley and Gilson, 2004;, leaving the direction of the causal relation unknown (De Spiegelaere et al, 2014). Fifth, we contribute to knowledge of internal flexibility practices in the Netherlands.…”
mentioning
confidence: 98%
“…The same goes for autonomy; if we find a significant effect, innovation managers should give employees enough discretion in how they perform their work tasks. For policy makers, this study could indicate that the observed rise in job insecurity in Europe is not a neutral process and can potentially negatively affect the innovation agenda (De Spiegelaere, Van Gyes & Van Hootegem, 2013).…”
Section: Introductionmentioning
confidence: 99%